A new foraging, post-breeding, and wintering site for the Mediterranean subspecies of the European Storm Petrel Hydrobates pelagicus melitensis in the Aegean Sea off Turkey. Issue 3 (2nd October 2022) - Onmuş, Ortaç; Ege, Turgut; Yoğurtçuoğlu, Emin; Bekir, Soner; Ekşioğlu, Süleyman
ABSTRACT: The Mediterranean subspecies of the European Storm Petrel Hydrobates pelagicus melitensis is suspected to be resident in the Aegean Sea off Turkey, but breeding is yet to be confirmed. Additionally, the area is used during the non-breeding season by individuals from elsewhere in the Mediterranean, and population sizes of over a thousand individuals have been recorded, especially in the central-south Aegean Sea.